2008
DOI: 10.1086/529419
|View full text |Cite
|
Sign up to set email alerts
|

Globular Clusters and X‐Ray Point Sources in Centaurus A (NGC 5128)

Abstract: We detect 353 X-ray point sources, mostly low-mass X-ray binaries (LMXBs), in four Chandra observations of Centaurus A (NGC 5128), the nearest giant early-type galaxy, and correlate this point-source population with the largest available ensemble of confirmed and likely globular clusters (GCs) associated with this galaxy. Of the X-ray sources, 31 are coincident with 30 GCs that are confirmed members of the galaxy by radial velocity measurement (two X-ray sources match one GC within our search radius), while on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 70 publications
(166 reference statements)
2
16
0
Order By: Relevance
“…It has been shown (see Fabbiano (2006) for a review) that a significant fraction of LMXBs observed in early-type galaxies with Chandra are associated with globular clusters (GCs). It has recently been confirmed that 41 X-ray point sources in our Cen A data are associated with GCs within Cen A (Woodley et al 2008;Jordán et al 2007;Voss et al 2009). We examined Spitzer/IRAC 3.6-and 8-µm IR maps (Hardcastle et al 2006) to check for IR counterparts to our jet knots, which would indicate a coincident globular cluster and found a compact IR source for GX3.…”
Section: Point Source Contaminationsupporting
confidence: 74%
“…It has been shown (see Fabbiano (2006) for a review) that a significant fraction of LMXBs observed in early-type galaxies with Chandra are associated with globular clusters (GCs). It has recently been confirmed that 41 X-ray point sources in our Cen A data are associated with GCs within Cen A (Woodley et al 2008;Jordán et al 2007;Voss et al 2009). We examined Spitzer/IRAC 3.6-and 8-µm IR maps (Hardcastle et al 2006) to check for IR counterparts to our jet knots, which would indicate a coincident globular cluster and found a compact IR source for GX3.…”
Section: Point Source Contaminationsupporting
confidence: 74%
“…This being the case, any attempt to perform optical photometry on the source position will be inconclusive. The nearest globular cluster that has been spectroscopically confirmed as belonging to Cen A is ∼30 away from CXOU J132527.6−430023 (Woodley et al 2008). However, no clusters have been detected within the radial distance of the transient from the galaxy center, as a result of the high stellar luminosity within ∼1.…”
Section: Possible Counterpartsmentioning
confidence: 99%
“…As this is steeper than the LF of the field LMXBs, to neglect their contribution may lead to artificially high confidence estimates. Furthermore, the study of Woodley et al (2008) did not take incompleteness effects into account, and they concluded that it was not clear if their analysis was not compromised by the sample incompleteness. The results presented above are therefore the most robust and statistically significant evidence yet for a difference between the luminosity distributions of LMXBs in the field and in globular clusters.…”
Section: Globular Cluster Sourcesmentioning
confidence: 99%
“…This suggestion has been confronted by the statistics of LMXBs and globular clusters in spiral galaxies and especially in the Milky Way. Also, evidence has been found that the luminosity distributions of LMXBs in globular clusters (and in the central parts of M 31) and in the field differ at the low luminosity end, below ∼ 10 37 erg s −1 , (Voss & Gilfanov 2007a;Fabbiano et al 2007;Woodley et al 2008;Kim et al 2009), which would be a strong indication of different formation histories.…”
mentioning
confidence: 97%
See 1 more Smart Citation